2019
DOI: 10.1177/0011000019893089
|View full text |Cite
|
Sign up to set email alerts
|

Ideology Matters: College Students’ Emotional Reactions to the Killing of Trayvon Martin

Abstract: Building on previous theory and research, we explored the associations among race, intergroup ideologies and emotional reactions to the killing of Trayvon Martin and the acquittal of George Zimmerman among 298 Black and White college students. We also examined the indirect effect of ethnocultural empathy on the links between race, intergroup ideologies, and emotional responding. Using latent class analysis, we identified three latent intergroup ideological classes: Racial Hierarchy-Enhancing Ideology, Universa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that critical consciousness is inversely related to social dominance theory (Thomas et al, 2014), yet another kind of system justification ideology. Blackmon et al (2019) found that college students with higher levels of awareness regarding prejudice reduced the effects of colorblindness on prosocial empathic responses.…”
Section: Colorblindnessmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have shown that critical consciousness is inversely related to social dominance theory (Thomas et al, 2014), yet another kind of system justification ideology. Blackmon et al (2019) found that college students with higher levels of awareness regarding prejudice reduced the effects of colorblindness on prosocial empathic responses.…”
Section: Colorblindnessmentioning
confidence: 96%
“…In a study (Blackmon et al, 2019) that explored both colorblindness and critical reflection, researchers conceptualized colorblindness as a race-specific indicator of system justification ideology. They defined a system justification ideology as one that seeks to maintain that hierarchical order of society.…”
Section: Colorblindnessmentioning
confidence: 99%
“…The majority of studies in this area focus on power evasion CBRI and have used the Scale of Ethnocultural Empathy (Wang et al, 2003). Medium associations have been found among helping professionals (Domenech Rodríguez et al, 2019) and medium-to-large effects among college students (Blackmon et al, 2019;Kleiman et al, 2015). It appears, however, that power evasion beliefs are not significantly related to the perspective-taking dimension of racial/ethnocultural empathy or the ability to cognitively understand the experiences of people who are racially or ethnically different than oneself (e.g., Kleiman et al, 2015).…”
Section: Empathymentioning
confidence: 99%
“…Much of the racism response literature identifies these emotions as common during and following an experience of racism (Carter, 2007; Harrell, 2000; Williams et al, 2019). Blackmon et al (2019) also reported how the racial group one belongs to explains differences in emotional responding to racially charged events. Though the VRHS was (a) not specifically directed at the participating students, (b) presented within a research/data collection context, and (c) participants were apprised of the racist language contained in the stimulus per the informed consent procedures, the content of the language, the use of stereotypes about Black people, the racial slurs, and the vitriol communicated in the five-minute audio clip was enough to elicit a negative affective experience for many of the participants.…”
Section: Discussionmentioning
confidence: 99%